The Attitude of the Community towards the Election of Members of the House of Representatives between Hua Takhe Community and Nongjok Community - ชุติกุลวรนันท์, ผกากรอง; สูติปัญญา, พรเทพ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to study the attitudes of communities towards exercising their right to vote in the parliamentary elections. The sample group consisted of 200 community members selected using convenience sampling. The research instrument was a questionnaire. The data was analyzed using percentages, means, standard deviations, and t-tests. The results showed that: 1) Community attitudes towards exercising their right to vote in the parliamentary elections were at a high level. Most community members considered exercising their right to vote in the parliamentary elections. 2) Regarding community attitudes towards exercising their right to vote in the parliamentary elections, there were significant differences between Huatakeh and Nongjok communities in terms of publicizing the election to acquaintances and helping to monitor the transparency of the elections in their districts, at a significance level of .05.